2017
DOI: 10.1016/j.eist.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A netnographic study of P2P collaborative consumption platforms’ user interface and design

Abstract: Although still embryonic, collaborative consumption and the sharing economy have become social and economic phenomena in just a few short years, yet there is little consensus on how to define them. The current classificatory schema or typologies of platforms have some weaknesses. Sectoral classifications, technological functionality, and discursive modes of understanding sharing and collaborative economies all provide valuable insights, but when taken individually important gaps are evident, not least in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 27 publications
1
49
0
4
Order By: Relevance
“…Most collaborative consumption practices are made easier by online platforms such as Airbnb facilitating accommodation rental (Bucher et al, 2016;Habibi et al, 2016;Huber, 2017;Zervas et al, 2017), or LeBonCoin facilitating goods rental and second-hand sales (Herbert and Collin-Lachaud, 2017;Parguel et al, 2017;Philip et al, 2015). The main activities of a dual-sided platform relate to optimizing the exchange organization between peers and their competitive objectives (i.e., two distinct but interdependent value propositions are formulated), designing a governance system, while creating trust and reducing the perceived risk of P2P exchanges de Rivera et al, 2017;Einav et al, 2016;Kumar et al, 2018;Muzellec et al, 2015;Perren and Kozinets, 2018;Rochet and Tirole, 2006). Herbert and Collin-Lachaud (2017) also found that collaborative consumption is a repertoire of practices unified by a unique practice style dominated by activities linked to commercial exchange, but that these transactions are also associated with the alternative ideas of community, gift-giving, solidarity, and generosity.…”
Section: Collaborative Consumption Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most collaborative consumption practices are made easier by online platforms such as Airbnb facilitating accommodation rental (Bucher et al, 2016;Habibi et al, 2016;Huber, 2017;Zervas et al, 2017), or LeBonCoin facilitating goods rental and second-hand sales (Herbert and Collin-Lachaud, 2017;Parguel et al, 2017;Philip et al, 2015). The main activities of a dual-sided platform relate to optimizing the exchange organization between peers and their competitive objectives (i.e., two distinct but interdependent value propositions are formulated), designing a governance system, while creating trust and reducing the perceived risk of P2P exchanges de Rivera et al, 2017;Einav et al, 2016;Kumar et al, 2018;Muzellec et al, 2015;Perren and Kozinets, 2018;Rochet and Tirole, 2006). Herbert and Collin-Lachaud (2017) also found that collaborative consumption is a repertoire of practices unified by a unique practice style dominated by activities linked to commercial exchange, but that these transactions are also associated with the alternative ideas of community, gift-giving, solidarity, and generosity.…”
Section: Collaborative Consumption Practicesmentioning
confidence: 99%
“…When peer providers and consumers exchange privately owned goods and services through online platforms, it is a collaborative consumption practice de Rivera et al, 2017;Hamari et al, 2016;Herbert and Collin-Lachaud, 2017;Huber, 2017;Möhlmann, 2015;Parguel et al, 2017). Belk (2014bBelk ( , p. 1597 explained that "collaborative consumption is the subset of Bardhi and Eckhardt's (2012) notion of access-based consumption" as participants access assets at the same time, not successively, so it is also called "consumer-to-consumer provision of access-based services" (Wilhelms et al, 2017, p. 39).…”
Section: Collaborative Consumption Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another platform typology is proposed by de Rivera et al (), Gordo, Cassidy, and Apesteguía () and contains three kinds of collaborative platforms: networking oriented, transaction oriented, and community oriented. Networking‐oriented platforms are based on a very large network and their primary purpose is to connect users through a sophisticated architecture.…”
Section: The Role Of the Internet And Ictsmentioning
confidence: 99%
“…In fact, the interface or platform design both conditions and predefines the social relations-related, for example, to interaction mechanisms, regulation, profile information, or promotion-among users [12,13].…”
Section: Previous Attempts To Classify Models Of Collaborative Economymentioning
confidence: 99%